9k-(-3k-7)=15

Simple and best practice solution for 9k-(-3k-7)=15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9k-(-3k-7)=15 equation:



9k-(-3k-7)=15
We move all terms to the left:
9k-(-3k-7)-(15)=0
We get rid of parentheses
9k+3k+7-15=0
We add all the numbers together, and all the variables
12k-8=0
We move all terms containing k to the left, all other terms to the right
12k=8
k=8/12
k=2/3

See similar equations:

| (6x+20)+(2x+4)=0 | | 49=x−48 | | 0.07g-6.5=0.2g | | 2x+56=4x-14 | | 3x-12=6x+5 | | -5x20=100 | | 7p+5p-3p=21+9-10 | | 7a−3=13a+7 | | -4+33=2x+81 | | -6(h+7)+8=-19 | | (6+6x)=-22x+2 | | -26=-10+8k | | (5u+10)=5 | | 4≤x+2≤=8 | | -10n-35=0 | | 8n-(4n+5)=9 | | -3=x-1-3 | | 11+21=-4(6x-8) | | (4n+19)-(6(n-9))=0 | | 83=21+m | | 8(y+2)+2y=-34 | | 5(x-5)=4(x+8) | | 2-6x-2=12 | | 2n+54-19=0 | | 8x-12=-71 | | 4=-2(1-3x)-6(x-1) | | 2+3(x1)=17 | | 1/5*(x-3)=3/4 | | -12=-2(r+5) | | -5/8v=20 | | 2(2-6x)=-68 | | n/13=-13 |

Equations solver categories